Students’ Perspective of the Use of WhatsApp Group as an Online Discussion Mode - Rifari Baron (STAI Hubbulwathan Duri, 2021)
It is believed that communication through technology applications is very important in the current learning situation. Among the utilized applications, WhatsApp presents as the most used application in the Indonesian teaching and learning circumstance. The purpose of this study was to find out the students’ perspective on the use of WA in-class discussion outside the classroom for postgraduate students in the Reading Learning course. The method used a descriptive qualitative case study. Data was taken from interviews and group discussion forums. Data analysis uses data reduction, data presentation, and concluding stages. The results showed that the WA group became a fairly effective medium at the level of student understanding for each of the teaching materials discussed. However, communication within the WA group requires standard rules agreed upon by each student so that the goal of forming a WA group as a learning medium outside the classroom can be achieved.